2021
DOI: 10.1001/jamaoncol.2020.6973
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Systemic Treatments for Metastatic Castration-Sensitive Prostate Cancer

Abstract: IMPORTANCE Multiple systemic treatments are available for metastatic castration-sensitive prostate cancer (mCSPC), with unclear comparative effectiveness and safety and widely varied costs.OBJECTIVE To compare the effectiveness and safety determined in randomized clinical trials of systemic treatments for mCSPC. DATA SOURCES Bibliographic databases (MEDLINE, Embase, and Cochrane Central), regulatory documents (US Food and Drug Administration and European Medicines Agency), and trial registries (ClinicalTrials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 44 publications
0
65
0
3
Order By: Relevance
“…Regarding the treatment of mCSPC patients, according to the network meta‐analysis, ADT plus Abi or Apa might provide the largest OS benefits, with relatively low serious AE risks. Enz might improve radiographic PFS to the greatest extent, but a longer follow up is required to examine the OS benefits associated with Enz 18 . Recently, Harada et al .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the treatment of mCSPC patients, according to the network meta‐analysis, ADT plus Abi or Apa might provide the largest OS benefits, with relatively low serious AE risks. Enz might improve radiographic PFS to the greatest extent, but a longer follow up is required to examine the OS benefits associated with Enz 18 . Recently, Harada et al .…”
Section: Discussionmentioning
confidence: 99%
“…Four published network meta-analysis studies have aimed to clarify this issue, of which two showed the utility of enzalutamide in OS 20,21 and the others demonstrated significant survival benefits of abiraterone in all patients. 22,23 Thus, the issue of which agent constitutes the best treatment choice is thus still controversial.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…For many years, first‐generation hormone therapy was the gold standard treatment for metastatic forms of prostate cancer. Since 2015, the advent of recent therapies, such as chemotherapy with docetaxel and second‐generation hormone therapies (abiraterone, enzalutamide, apalutamide) have enriched the management options for metastatic prostate cancer, with an improvement in overall and progression‐free survival (PFS) 7–12 …”
Section: Introductionmentioning
confidence: 99%